IS ENVIRONMENTALLY-FRIENDLY PRODUCT PURCHASE INTENTION OF CRUELTY-FREE SKINCARE AFFECTED BY ENVIRONMENTAL RESPONSIBILITY? - Nuari, Karunia Putri; Dhewi, Titis Shinta (Departemen Manajemen Fakultas Ekonomi dan Bisnis Universitas Negeri Malang, 2023)
This study aims to determine the effect of environmental responsibility on environmentally-friendly product purchase intention with price sensitivity as a moderator. The research subjects are young generation who are interested to buy The Body Shop, Lacoco, and Avoskin skincare. The purposive sampling technique yielded 150 respondents for the research sample. This research is descriptive explanatory, and the method of collecting data is through the distribution of questionnaires to respondents. The analytical technique is an SEM of PLS assisted by SmartPLS 4.0. The study’s result found that there was a direct effect of environmental responsibility and environmentally-friendly purchase intention that positively affected young consumers of The Body Shop, Lacoco, and Avoskin. In addition, it is known that environmental responsibility has positively impact environmentally-friendly purchase intention. Also, the moderating role of price sensitivity for the relation of environmental responsibility and environmentally-friendly purchase intention has been accepted.